Carbon dioxide laser: a novel approach for vallecular cyst excision in pediatric population - Shendge, Neha Anand; Panja, Shantanu; Bose, Alokendu; Ghosh, Suvojit (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2024)
In the pediatric population, vallecular cysts are most commonly found at the base of the tongue and the vallecula. They may present with sudden, life-threatening airway obstructions due to their anatomical position. A 4-year-old presented with a change in voice from the past 2 months and was diagnosed with a vallecular cyst. The patient was planned to undergo CO2 laser micro-laryngeal surgery due to its precision and accuracy. In postoperative studies, the emerging CO2 laser technology demonstrated superior results. In particular, in complex cases, this innovative approach has the potential to achieve the desired results.